Oxidation of D-lactate and L-lactate by Neisseria meningitidis: purification and cloning of meningococcal D-lactate dehydrogenase. - Erwin, A L (1993)
Neisseria meningitidis was found to contain at least two lactate-oxidizing enzymes. One of these was purified 460-fold from spheroplast membranes and found to be specific primarily for D-lactate, with low-affinity activity for L-lactate. The gene for this enzyme (dld) was cloned, and a dld mutant was constructed by insertional inactivation of the gene. The mutant was unable to grow on D-lactate but retained the ability to grow on L-lactate, providing evidence for a second lactate-oxidizing enzyme with specificity for L-lactate. High-affinity L-lactate-oxidizing activity was detected in intact bacteria of both the dld+ and dld mutant strains. This L-lactate-oxidizing activity was also seen in sonicated bacteria but was reduced substantially on detergent solubilization or on preparation of spheroplast membranes.